Analysis Of Occupational Safety and Health Risk on The Pineapple Farmers Tangkit Baru Village Using The Method Job Safety Analysis : Analisis Risiko Keselamatan dan Kesehatan Kerja pada Petani Nanas Desa Tangkit Baru Menggunakan Metode Job Safety Analysis - Rizka Nabila (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Background: Indonesia is an agricultural country because some of the population works as farmers. Pineapple is one of the fruit commoditties that makes a major contribution to horticulture production. The pineapple farmer is an informal sector worker who is at risk of obtaining potential hazards from his job. Working farmers still have not implemented the importancce of using APD in the workplace and the lack of understanding of safety issues that lead to increased risk of work accidents. Objectives: This research was conducted to identify potential hazards and assess Occupational Safety and Health (K3) risks using the Job Safety Analysis (JSA) method among Pineapple Farmers in Tangkit Baru Village. Research Metodes: This research uses qualitative methods. This study was conducted on the Nanas Farmers of the New Infectious Village in January-May 2024. A total of nine research informants were identified with purposive sampling techniques. Data collection was done with in-depth interviews and observations. Results: This study analyzed the risk to safety and health at work in Nanas Farmers and the findings of this study include: (1) Identification of hazards in the process of spraying pesticides with 5 activities there are 5 hazards and in the harvest process with 4 activities there is 6 hazards, (2) Risk control is carried out with administrative distribution such as tool safety inspection and for the use of PPE such as use of protective equipment such as cloth gloves, fabric masks, and safety shoes. Conclusion: Identification of hazards in spraying pesticides and harvesting has 5 activities with 5 hazards and 4 activities with 6 hazards. Recommended hazard control measures are self-protection devices (APD). Keywords: Hazard Identification; Risk Assessment; Risk Control; Job Safety Analysis (JSA); Pineapple Farmers